Policy Recommendation for Industrial Area Development based on Environment Carrying Capacity in The Northern Coast of Tuban, Indonesia - Eko Budi Santoso; Raga Bagas Pratama; Nabila Azzahra Tiara Diska; Amrih Eka Pratiwi (Jurnal Penataan Ruang, 2025)
The development of industrial areas is one of the main strategies in supporting national economic growth but also has various impacts that need to be managed carefully. This study focuses on the analysis of the development of industrial areas on the coast of Tuban and its impacts on the environment, infrastructure, and local economy. This study also explores the harmony of land and coastal land use, which is an important factor in ensuring sustainable and integrated development. This study analyzes the development of coastal industrial areas in Tuban and its impacts on the environment, infrastructure, and local economy. The focus is the integration of land and coastal land use to support sustainable development. Through a spatial analysis approach, literature review, and stakeholder interviews, it was found that coastal area development has the potential to cause ecosystem degradation, increased disaster risk, and pollution. Other challenges include infrastructure needs, minimal local economic growth (PAD) and limited skills of the local workforce. This study recommends spatial planning policies, environmental management, and inclusive economic programs to ensure equitable and sustainable development in the coastal area of Tuban.